STUDENTS’ PROFILE ON ABILITY TO EXPLAIN BASIC CONCEPTS ON BIOLOGY OF THE CELL COURSE - Fernando, Adam; Fauziah, Nurul (JURNAL EDUSCIENCE, 2024)
The low quality of students' understanding of basic concepts in cell biology courses is reflected in the quality of students when explaining these concepts in class. Therefore, there was a need for information regarding student profiles to explain basic concepts of cell biology. This research aimed to describe the student's profile. This quantitative descriptive research involved 41 students from the UMRAH Biology Education Study Program who took the Cell Biology course in the odd semester of 2023-2024. This research used observation sheets to observe explanation skills. Based on the results and discussion obtained, the student profile regarding skills in explaining basic concepts of cell biology is in the less skilled category. Keywords: Ability; Explain; Concepts; Biology; Cell Abstrak Kualitas pemahaman mahasiswa yang rendah tentang konsep-konsep dasar pada mata kuliah biologi sel tercermin dari kualitas mahasiswa ketika menjelaskan konsep-konsep tersebut di dalam kelas. Oleh karena itu, perlu adanya informasi mengenai profil mahasiswa tentang keterampilan menjelaskan konsep-konsep dasar biologi sel. Penelitian ini bertujuan untuk mendeskripsikan profil mahasiswa tersebut. Penelitian deskriptif kuantitatif ini melibatkan mahasiswa Program Studi Pendidikan Biologi UMRAH yang mengikuti mata kuliah Biologi Sel di semester ganjil 2023-2024 sebanyak 41 orang. Penelitian ini menggunakan lembar observasi untuk mengamati keterampilan menjelaskan. Berdasarkan hasil dan pembahasan yang diperoleh, maka dapat disimpulkan bahwa profil mahasiswa tentang keterampilan menjelaskan konsep-konsep dasar biologi sel berada pada kategori kurang terampil. Kata Kunci: Keterampilan; Menjelaskan; Konsep; Biologi Sel